Associations between cardiovascular health and female infertility: A national population-based study - Luo, Meiyan; Li, Jianshu; Xiao, Xiangjun; Wu, Ping; Zhang, Ya (PloS one, 2024)
This study investigates the relationship between cardiovascular health (CVH), as quantified by the American Heart Association's Life's Essential 8 (LE8) metric, and female infertility, utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2013-2018. We encompassed females aged 20-49 years and above from the NHANES in this cross-sectional analysis. We assessed CVH using the LE8 score, encompassing eight domains: dietary pattern, physical activity, nicotine exposure, sleep duration, body mass index (BMI), lipid profile, fasting blood glucose, and blood pressure levels. Logistic regression models were applied to explore the association between CVH scores and reported infertility, adjusting for potential confounders including age, race/ethnicity, and socioeconomic status. Findings revealed a notable inverse association between CVH scores (per 10 scores) and female infertility [OR = 0.93, 95%CI: 0.90-0.96], Participants with higher CVH levels were 41% less likely to had female infertility compared to those with lower levels [OR = 0.59, 95%CI: 0.41-0.84]. Higher overall CVH scores, particularly in physical activity, BMI, and blood glucose, were associated with lower odds of infertility. This trend remained consistent across various demographic subgroups. Our findings underscore the significance of maintaining optimal cardiovascular health, as evidenced by higher LE8 scores, in mitigating the risk of female infertility. These insights advocate for the integration of CVH improvement strategies within the broader framework of reproductive health care, emphasizing the dual benefits of cardiovascular and reproductive health optimization.